2009
DOI: 10.1210/en.2008-0999
|View full text |Cite
|
Sign up to set email alerts
|

Selective Elevation of Adiponectin Production by the Natural Compounds Derived from a Medicinal Herb Alleviates Insulin Resistance and Glucose Intolerance in Obese Mice

Abstract: Adiponectin is an adipocyte-derived insulin-sensitizing hormone with antidiabetic, antiinflammatory, and antiatherosclerotic properties. A decreased serum level of adiponectin in obesity has been identified as an independent risk factor for diabetes and cardiovascular complications, suggesting that pharmacological intervention aimed at elevating adiponectin production might hold promise for the treatment and/or prevention of these diseases. Here we report the identification of two structurally related natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 42 publications
1
62
0
Order By: Relevance
“…Studies which focused on both dietary and genetically obese mice treated with AM (root) derivatives have shown significant increases in circulating adiponectin in association with potent reduction in insulin resistance and glucose intolerance, suggesting that AM (root) may be a therapeutic candidate for the treatment of obesity-related disease (Xu et al, 2009). AM (root) was able to reverse hyperglycemia and protect pancreatic islets in type 1 DM in NOD mice by changing the predominant form of lymphocytes/cytokines from Th1 to Th2, thus preventing lymphocyte infiltration of the pancreas (Chen et al, 2008a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Studies which focused on both dietary and genetically obese mice treated with AM (root) derivatives have shown significant increases in circulating adiponectin in association with potent reduction in insulin resistance and glucose intolerance, suggesting that AM (root) may be a therapeutic candidate for the treatment of obesity-related disease (Xu et al, 2009). AM (root) was able to reverse hyperglycemia and protect pancreatic islets in type 1 DM in NOD mice by changing the predominant form of lymphocytes/cytokines from Th1 to Th2, thus preventing lymphocyte infiltration of the pancreas (Chen et al, 2008a,b).…”
Section: Discussionmentioning
confidence: 99%
“…To establish a dietary obese mouse model, 4-week-old male C57BL/6J mice were fed a 19.33 kJ/g high fat diet (D12451, Research Diet, New Brunswick, NJ) containing 45 Kcal % fat, 20 Kcal % protein, and 35 Kcal % carbohydrate for 10 weeks as described previously (24). For the intraperitoneal glucose tolerance test, mice that were fasted overnight (16 h) were given a glucose load by intraperitoneal injection (1 g of glucose/kg of body weight).…”
Section: Methodsmentioning
confidence: 99%
“…A decreased adiponectin serum level in obese patients has been identified as an independent risk factor for diabetes and cardiovascular complications. (41) Research by Xu, et al (42) suggested that astragaloside Ⅱ and isoastragaloside Ⅰ from the medicinal herb Radix Astragali increased adiponectin secretion. Adenosine monophosphate-activated protein kinase (AMPK) had cardioprotective effects against ischemic injury and the forkhead transcription factor 3 (FOXO3) had been identified as a downstream marker of AMPK.…”
Section: Treatment Of Diabetes With Chinese Medicines Against Multiplmentioning
confidence: 99%